Factors Associated with Fatigue and Excessive Daytime Sleepiness in Professionals Working in Mobile Emergency Care Service - Campos, Alessandra Batista de; Junqueira, Isabela Cinquini; Borges, Leonardo Luiz; Cordeiro, Jacqueline Andréia Bernardes Leão; Silva, Antonio Márcio Teodoro Cordeiro; Almeida, Rogério José de (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Objective: Analyze factors associated with fatigue and excessive daytime sleepiness among professionals of the Mobile Emergency Care Service (SAMU) of the Federal District/Brazil. Methods: This is a cross-sectional analytical study with a quantitative approach. Data were obtained from a questionnaire and two scales used for sociodemographic, fatigue and sleepiness data collection. Descriptive statistics and statistical tests were used for data analysis. Results: 323 professionals participated in this research: nurse technician, nurse, driver, and doctor. Our results demonstrated the prevalence of male professionals (64.7%), age < 40 years (51.4%), married (64.1%), nurse technician (43.7%). The highest level of fatigue rates was observed in female professionals (p <0.001), without physical activity (p = 0.004), nurse technician (p <0.001), dissatisfied with their job (p <0.001). The highest rates of sleepiness were observed in nurse technicians (p <0.001) and females (p = 0.015). Conclusion: There is a positive correlation between fatigue and excessive daytime sleepiness, as well as several factors that are associated with higher scores in these two conditions that affect SAMU-DF Pre-Hospital Care professionals.